Penggunaan Media â€œPeta Buta Elektronikâ€ Terhadap Pengetahuan Peta Buta Siswa Sekolah Dasar - wulan dewi andhari; muzani muzani; asma irma setianingsih (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2017)
This research aims to find an empirical answers about the different knowledge of student’s blank map by using “Peta Buta Elektronik“ on the subjects of social science education.The research was conducted at SDIT AN-Nadwah Bekasi. The method used is an experimental method. The sampling technique is purposive sampling. With the research criteria samples which is taught by the same teacher, has taught the same material, and also has the same level of value achievement. The instrument used in this study is in the form of a multiple choice test which is pre test and post test.The results showed that there were differences between the students knowledge of blank map among the experimental class which using an “Peta Buta Elektronik“ and the controls class which did not use the “Peta Buta Elektronik“ on the natural appearance material also the social and cultural diversity. There is an increase in the average value of 15.22 in the experimental class, whereas the control group had increased by an average of 13.00. The existence of a significant difference to the knowledge of blank mapis evidenced by the t test and obtained = 2.41 and with dk/hp 58 and a significance level of 0.05 is 1.67. So > meaning that the alternative hypothesis is accepted while the null hypothesis is rejected. Based on this study it is known that there are differences inknowledge of student’s fourth grade blank map by using the “Peta Buta Elektronik“. Therefore, the teachers of social science education are able to use this “Peta Buta Elektronik“ as one of the media used in teaching and learning process, especially on the natural appearance material also the social and cultural diversity. Keywords: Media of Education, Knowledge of the Blank Map, Peta Buta Elektronik